Dążenie patronów Archidiecezji Poznańskiej do pełni życia w Bogu - Hadryś, Jacek (Poznańskie Studia Teologiczne, 2018)
The article presents the pursuit of the fullness of life in God by the saint patrons of the Archdiocese of Poznan, namely the saint bishop and martyr Stanislaw of Szczepanow, the blessed bishop and hermit Bogumil and the saint sister Urszula Ledochowska. The presentation is done according to the scheme: determinants of spiritual life — the most important elements and manifestations of sanctity. The inferences and assertions resulting from the conducted analyses are included in the conclusion. The study is preceded by a recapitulation of the basic truths regarding Christian spir- itual life and the role of saints in the lives of Christians. Studies have shown, among other things, that each of the patrons came into the world in a family with a deep faith and received a vocation to dedicate their life to God. In saint Stanislaus and saint Urszula you can see great organizational talents, a very friendly and gentle reference to others, concern for those in need of help and support, and the greatness of their dedication to others. In blessed Bogumil, the most noticeable feature is his love for hidden life and the practice of severe penance. All three share a commitment to evan- gelization. Each of them reveals a passion for prayer, a concern for being in deep communion with Christ, living with Christ and for Him the experience of suffering and awareness of responsibility for the salvation of others, as well as distance to material goods.